TINJAUAN HUKUM BAGI PELAKU TINDAK PIDANA PORNOGRAFI BERDASARKAN UNDANG - UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Dodo Preacher Simorangkir,; Wiwik Sri Widiarty,; Andrew Betlehn, (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Criminal law is very important in regulating crimes committed through various types and tactics. The Criminal Code must be the appropriate way to execute criminals. Several types of criminal acts include pornography which is regulated in Law Number 44 of 2008 and ITE which is regulated in Law Number 19 of 2016. The research method in this thesis uses legal research methods, especially normative juridical methods, while the research approach technique uses legal research techniques. Legal sources come from legal studies using primary, secondary and tertiary legal texts. Techniques for collecting legal resources through the study of relevant literature to resolve these difficulties. Based on research findings, law enforcement should target perpetrators of criminal acts of pornography based on Law Number 44 of 2008 and its distribution through electronic media based on Law Number 19 of 2016.